Safe Haskell | None |
---|

Definition of the `LaTeXC`

class, used to combine the classic applicative and
the latter monadic interfaces of *HaTeX 3*. The user can define new instances
as well, adding flexibility to the way *HaTeX* is used.

- class (Monoid l, IsString l) => LaTeXC l where
- class Monoid a where
- fromLaTeX :: LaTeXC l => LaTeX -> l
- liftL :: LaTeXC l => (LaTeX -> LaTeX) -> l -> l
- liftL2 :: LaTeXC l => (LaTeX -> LaTeX -> LaTeX) -> l -> l -> l
- liftL3 :: LaTeXC l => (LaTeX -> LaTeX -> LaTeX -> LaTeX) -> l -> l -> l -> l
- comm0 :: LaTeXC l => String -> l
- commS :: LaTeXC l => String -> l
- braces :: LaTeXC l => l -> l

# Documentation

class Monoid a where

The class of monoids (types with an associative binary operation that has an identity). Instances should satisfy the following laws:

mappend mempty x = x

mappend x mempty = x

mappend x (mappend y z) = mappend (mappend x y) z

mconcat =

`foldr`

mappend mempty

The method names refer to the monoid of lists under concatenation, but there are many other instances.

Minimal complete definition: `mempty`

and `mappend`

.

Some types can be viewed as a monoid in more than one way,
e.g. both addition and multiplication on numbers.
In such cases we often define `newtype`

s and make those instances
of `Monoid`

, e.g. `Sum`

and `Product`

.

mempty :: a

Identity of `mappend`

mappend :: a -> a -> a

An associative operation

mconcat :: [a] -> a

Fold a list using the monoid.
For most types, the default definition for `mconcat`

will be
used, but the function is included in the class definition so
that an optimized version can be provided for specific types.

Monoid Ordering | |

Monoid () | |

Monoid ByteString | |

Monoid Text | |

Monoid More | |

Monoid All | |

Monoid Any | |

Monoid Text | |

Monoid LaTeX | Method |

Monoid TeXCheck | |

Monoid [a] | |

Monoid a => Monoid (Maybe a) | Lift a semigroup into |

Monoid t => Monoid (Input t) | |

Monoid t => Monoid (Added t) | |

Monoid a => Monoid (Dual a) | |

Monoid (Endo a) | |

Num a => Monoid (Sum a) | |

Num a => Monoid (Product a) | |

Monoid (First a) | |

Monoid (Last a) | |

Monoid b => Monoid (a -> b) | |

(Monoid a, Monoid b) => Monoid (a, b) | |

Monoid t => Monoid (Parser t a) | |

Monad m => Monoid (LaTeXT m a) | |

(Monoid a, Monoid b, Monoid c) => Monoid (a, b, c) | |

(Monoid a, Monoid b, Monoid c, Monoid d) => Monoid (a, b, c, d) | |

(Monoid a, Monoid b, Monoid c, Monoid d, Monoid e) => Monoid (a, b, c, d, e) |

# Combinators

## From `LaTeX`

## Lifting

Lifting functions from `LaTeX`

functions to functions over any instance of `LaTeXC`

.
In general, the implementation is as follows:

liftLN f x1 ... xN = liftListL (\[x1,...,xN] -> f x1 ... xN) [x1,...,xN]

liftL2 :: LaTeXC l => (LaTeX -> LaTeX -> LaTeX) -> l -> l -> lSource

Variant of `liftL`

with a two arguments function.

liftL3 :: LaTeXC l => (LaTeX -> LaTeX -> LaTeX -> LaTeX) -> l -> l -> l -> lSource

Variant of `liftL`

with a three arguments function.